Testing a Model of Intercultural Willingness to Communicate based on Ethnocentrism, Ambiguity Tolerance and Sensation Seeking: The Role of Learning English in Iran. Issue 4 (3rd July 2016) - Hosseini Fatemi, Azar; Khajavy, Gholam Hassan; Choi, Charles W.
Abstract: The present study aimed at testing a model of intercultural willingness to communicate based on ethnocentrism, ambiguity tolerance and sensation seeking between English and non-English major university students in Iran. A significant difference was found between the two groups on ethnocentrism and the results showed that the model fit the data adequately. Ethnocentrism was the strongest predictor of intercultural willingness to communicate for both groups. Sensation seeking was a significant predictor of intercultural willingness to communicate only for the non-English major university students. Moreover, sensation seeking and ambiguity tolerance were significant predictors of ethnocentrism.